Portable magic a history of books and their readers - Smith, Emma 1970- (Alfred A. Knopf, 2022)
"Most of what we say about books is really about the words inside them: the rosy nostalgic glow for childhood reading, the lifetime companionship of a much-loved novel. But books are things as well as words, objects in our lives as well as worlds in our heads. And just as we crack their spines, loosen their leaves and write in their margins, so they disrupt and disorder us in turn. All books are, as Stephen King put it, 'a uniquely portable magic'. Here, Emma Smith shows us why"--
"Originally published in by Allen Lane, an imprint of Penguin Random House UK., in London in 2022.
Keywords: Geschichte; Aussehen; Ausstattung; Design; Materialität; Buch; Books / History; Books and reading / History; Book industries and trade / History; Books / Anecdotes; Books and reading / Anecdotes; Book industries and trade; Books; Books and reading; Anecdotes; History